2017
DOI: 10.5195/cajgh.2017.277
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Trends of Waterborne Diseases in Tashkent Province

Abstract: Introduction: The cumulative effect of limited investment in public water systems, inadequate public health infrastructure, and gaps in infectious disease prevention increased the incidence of waterborne diseases in Uzbekistan. The objectives of this study were:(1) to spatially analyze the distribution of the diseases in Tashkent Province, (2) to identify the intensity of spatial trends in the province, (3) to identify urban-rural characteristics of the disease distribution, and (4) to identify the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…An outbreak investigation of contaminated water supply in Greece similarly found that the majority of cases (6 of 11) had multiple pathogens detected in their stool [6]. Contamination of the water distribution system that has not been properly treated or maintained has been implicated in other outbreaks of water diseases in the region [7][8][9][10]. Lack of quality control of drinking water likely also contributed to the in a rural village outbreak [11].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…An outbreak investigation of contaminated water supply in Greece similarly found that the majority of cases (6 of 11) had multiple pathogens detected in their stool [6]. Contamination of the water distribution system that has not been properly treated or maintained has been implicated in other outbreaks of water diseases in the region [7][8][9][10]. Lack of quality control of drinking water likely also contributed to the in a rural village outbreak [11].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Water supply systems in post-soviet countries have suffered from lack of maintenance and deterioration in rural areas. For example, a study in Uzbekistan found that risk for waterborne diseases in Uzbekistan is greater in rural areas [7]. The investigation found that the monitoring of the quality and safety of water according to national regulations had not been carried out since 2018, neither by the organization involved in the maintenance of the water supply facilities and the distribution network of the village nor by the supervisory.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…This has a significant impact on human health. A spatial temporal analysis in the province revealed that the province is vulnerable to four major water-borne diseases: enterobiasis, hepatitis A, acute intestinal infection, and dysentery [ 16 ]. The incidence rates for enterobiasis were found to be highest, with a four-year (2011–2014) average of about 1084 cases per 100,000 population; the lowest were for dysentery, with an average of 28 cases per 100,000 population.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Although the district receives water from the two rivers (Chirchik and Akhangaran), the ground water drawn from the wells along the Akhangaran river remains the main water source. In this district, Olmalik city was selected for study as it reported the highest incidence of WTDs in the province between 2011 and 2014 [ 16 ]. The average incidence rates of acute intestinal infections and hepatitis A were about 296 and 250, respectively, between 2011 and 2014.…”
Section: Study Backgroundmentioning
confidence: 99%